2013
DOI: 10.4088/pcc.12r01464
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Body Dysmorphic Disorder and Its Presentation in Different Clinical Settings

Abstract: A considerable overlap exists between BDD and other psychiatric disorders such as OCD, anxiety, and delusional disorder, and this comorbidity should be considered in evaluation, management, and long-term follow-up of the disorder. Individuals with BDD usually consult dermatologists and cosmetic surgeons rather than psychiatrists. Collaboration between different specialties (such as primary care, dermatology, cosmetic surgery, and psychiatry) is required for better treatment outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
14

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 45 publications
1
36
0
14
Order By: Relevance
“…Also, self-concept clarity, thin-ideal internalization and the appearance-related social comparison among peers are important as predictors of body dissatisfaction, all of the factors of the so-called "tripartite influential model" (8). It is noteworthy that body dysmorphic disorders have a negative impact in mental health and quality of life in those whom suffer them, but also, they become prone to other diseases, including death (2,9).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, self-concept clarity, thin-ideal internalization and the appearance-related social comparison among peers are important as predictors of body dissatisfaction, all of the factors of the so-called "tripartite influential model" (8). It is noteworthy that body dysmorphic disorders have a negative impact in mental health and quality of life in those whom suffer them, but also, they become prone to other diseases, including death (2,9).…”
Section: Introductionmentioning
confidence: 99%
“…During this period, several lifestyle changes occur in youth related to their own body self-perception, due to the acquisition of stereotype habits and the social desire to be "in good shape" associated to social models imposed by the mass media (1), while sedentarism and consumption of energy-dense nutrient-low foods are also prevalent at this age. In addition, youth are resistant to behavioral change (3,4), experiencing a plethora of abnormal eating behaviors and body dysmorphic disorders (BDD) (2,5). According to the Diagnostic and statistical manual of mental disorders (DSM-5), preoccupation with flaw in appearance associated to repetitive behaviors, distress, impairment with or without a clinically defined eating disorder are major symptoms of BDD (6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A contributing factor to the low level of awareness among healthcare professionals is that individuals with BDD are often secretive about their symptoms because they believe that they will be viewed as vain or narcissistic (Mufaddel et al, 2013). Moreover, most BDD sufferers have poor insight into their illness; several studies have reported that 30 to 60% are delusional regarding their perceived appearance dlaws (Phillips et al, 2001;Crerand et al, 2005;Phillips et al, 2010a).…”
Section: An Under-recognized Disordermentioning
confidence: 99%
“…They have a pervasive feeling of ugliness and are convinced that some part of their body is defective (Mufaddel et al, 2013). The most frequent areas of concern are the face and head, and the main worries are related to problems such as acne, wrinkles, scars, the size and shape of the nose or ears, asymmetric or disproportional face, thinning hair or excessive facial hair.…”
Section: Interviewee In Study IVmentioning
confidence: 99%